Review of the genus Macroscirtus Pictet, 1888 (Orthoptera: Tettigoniidae) with the description of a new species - Simeu-Noutchom, Alain; Heller, Klaus-Gerhard; Affa'a, Glwadys Zang; Wandji, Alain Christel; Nzike, Marcelle Mbadjoun (Zootaxa, 2022)
The genus Macroscirtus belongs to the subfamily Mecopodinae with five recognized species distributed in central-west tropical Africa. All species are known from very few localities. The species are reviewed and, in addition, a new species from Cameroon is described. Macroscirtus kekeunoui sp. nov. is characterized by the tegmina not reaching the penultimate abdominal segment; hind femura with mottled brown external face, ventral and internal face completely pale yellow; male subgenital plate elongated horizontally, indentation edge straight. Species descriptions of the genus are documented and a key to the species is also provided.